A step variational iteration method for solving non-chaotic and chaotic systems - Yulita Molliq, R; Noorani, M.S.M.; Ahmad, R.R.; Alomari, A.K. (Universiti Kebangsaan Malaysia, 2013)
In this paper, a new reliable method called the step variational iteration method (SVIM) based on an adaptation of the variational iteration method (VIM) is presented to solve non–chaotic and chaotic systems. The SVIM uses the general Lagrange multipliers for constructing the correction functional for the problems. The SVIM yields a step analytical solution of the form of a rapidly convergent infinite power series with easily computable terms and obtain a good approximate solution for larger intervals. The accuracy of the presented solution obtained is in an excellent agreement with the previously published solutions.